The Effect of Physical Activity and Gestational Weight Gain on Lipid Markers Throughout Pregnancy: Does One Outweigh the Other? - Catherine, Everest (Université d'Ottawa / University of Ottawa, 2022)
Background: In the pregnant population, being physical active and meeting gestational weight gain (GWG) guidelines have numerous health benefits for both mother and infant. Markers of lipid metabolism are known to be influenced by these two variables in the non-pregnant population. However, the relationship between physical activity (PA) and GWG on lipid markers has yet to be assessed during pregnancy. My thesis aims to address this gap in the literature. Methods: The first objective of my thesis was to examine the relationship between maternal PA and GWG on gross measurements of fetal and placental development (n=40). Specifically, three markers of placental efficiency (Pl-E) were examined (birthweight [BW], BW-to-placenta weight ratio, and residual BW). The second objective of my thesis was to analyze maternal serum lipid and glucose markers (n=40), in mid (24-28 weeks) and late (34-38 weeks) gestation as well as from the umbilical cord (UC) as they relate to both PA and GWG. The third objective of my thesis was to explore how PA level and GWG status affect markers of lipid metabolism in term placenta (n=31). Markers of placental lipid transport (FATP1, FABP4, FAT/CD36) were assessed at the protein level, and enzymatic activity of placental lipoprotein lipase was also measured. Lastly, placental lipid storage was assessed by examining triglyceride content, paired with lipid droplet staining. Results: There was no relationship between PA independently or in combination with GWG on any Pl-E markers. A significant association was found between GWG and BW in women who gained weight excessively compared to insufficiently. Neither PA nor GWG categorization was associated with maternal lipid and glucose markers. Total cholesterol levels measured in UC serum were significantly lower in women categorized as active throughout pregnancy (p<0.0001) or whose activity dropped in late gestation (p<0.0001) compared to those who were inactive v throughout gestation. Glucose levels were lower in UC blood of women who gained weight appropriately in mid-gestation compared to those who gained insufficient (p=0.040) or excessive (p=0.021) weight. In terms of placental fatty acid transport, there was a significant interaction between PA status and GWG categorization and placental FATP1 protein expression (F=14.62, p<0.0001). Finally, while no differences were found in placental lipid droplet staining, the droplets were more likely to be clustered within the syncytiotrophoblast border. Conclusion: In conclusion, maternal PA had no association with Pl-E, while GWG was only associated with BW. My thesis work found that while maternal serum lipid markers were not associated with PA and GWG, both maternal PA and GWG status were related to changes in UC and placental lipid markers throughout pregnancy. In combination with previous research from our lab, it is suggested that women who are physically active during pregnancy, and gain weight appropriately may be transporting fewer nutrients (i.e. fatty acid, glucose, cholesterol) to the placenta than those who are inactive, yet simultaneously increasing metabolization. Future research should further investigate these findings by performing functional experiments.
Keywords: Pregnancy; Placenta; Lipid; Neonatal; Physical Activity; Gestational Weight Gain